Cape Anne: Its physical and environmental geology - Ross, Martin E. (2015)
"Cape Anne, Massachusetts has long been famous for its spectacular scenery and intriguing geology. This volume, written by a long time resident and geologist, brings to life the secrets of Cape Anne's geology as well as the environmental impact current and past land use has had on the cape from a geological perspective. Also included is a geologic field guide to ten fascinating localities along the rocky shore." - From the book cover. To obtain a copy, contact Martin Ross at m.ross@neu.edu The book is also available on Amazon.com
Keywords: #Fieldtrips; #MassGeology; #MassGeologyBooks; Anneite; Cape Anne; diabase; dikes; Dogtown; dogtown morraine; erratics; gabbro; Gloucester; granite; Halibut Point; Manchester by the Sea; morraine; phenocrysts; Rafe's Chasm; Rockport

The Flow of Time - 500 Million Years of Geohistory in the Connecticut River Valley (Earthview LLC, 2000)
With animations and a bit of humor, geologist-educator Richard Little takes you through the amazing events of the last 500 million years in the Connecticut River Valley region, and shows you why this is the best place to study geology in the world. Learn about glacial Lake Hitchcock, unique armored mud balls and take a tour of the dinosaur resources of the Amherst College Pratt Museum and Dinosaur State Park, Rocky Hill, CT. This video has been seen by thousands and is in use in classrooms from upper elementary school through college.
Keywords: #ConnecticutValley; #EducationalResources; #MassGeology; #MassGeologyBooks; armored mudballs; book; clay; Connecticut Valley; dinosaurs; field trip guide; footprints; fossils; geologic history; glacial lake; glaciers; hitchcock; mesozoic; movie; mud balls; mudballs; nNew England; site; varves; video; western Massachusetts

The Rise and Fall of Lake Hitchcock - New England's Greatest Glacial Lake (Earthview LLC, 2000)
Prof. Richard Little hosts this 45-minute program, filled with air views, diagrams, animations, spectacular glacial locations from Canada to Alaska, some humor, and interviews with important geologists, investigating such things as groundwater, varved clay, concretions, sand dunes, pingos, and the nature and destruction of the Lake Hitchcock dam in central Connecticut. You will see how Lake Hitchcock was the most important event to shape the natural and human history of the Connecticut Valley.
Keywords: #ConnecticutValley; #EducationalResources; #MassGeology; #MassGeologyBooks; book; clay; Connecticut Valley; field trip guide; geologic history; glaciers; lake hitchcock; movie; nNew England; site; video; western Massachusetts

Dinosaurs, Dunes, and Drifting Continents: the Geohistory of the Connecticut Valley (Earthview LLC)
Written by local geology expert Richard Little, this book is a great resource for the geologic layperson interested in the geologist history of the Connecticut Valley: from its formation during the rifting of Pangea through the modification of the landscape by glaciers during the most recent ice age.
Keywords: #ConnecticutValley; #EducationalResources; #MassGeology; #MassGeologyBooks; book; clay; Connecticut Valley; dinosaurs; field trip guide; footprints; fossils; geologic history; glaciers; hitchcock; lake; mesozoic; New England; site; varves; western Massachusetts

The Dynamic Digital Map of New England by Chris Condit (U-Mass, Amherst) (U-Mass Geosciences)
This program presents four thematic maps of Massachusetts, in five overlapping segments, including the State Geologic Map. It also contains maps of four more limited areas that include six geologic field trips, with field trip routes and stops delineated on the maps and linked to Field Guides describing the geology seen at each stop. Linked to the maps and guide articles are 330 images, many oblique aerial photos taken by Chris Condit, used to illustrate the geology and scenic nature of this region.
Keywords: #ConnecticutValley; #EducationalResources; #Fieldtrips; #MassGeology; #MassGeologyBooks; book; field trip guide; geologic history; guidebook; online; site; virtual

Exploring the Berkshire Hills: A Guide to Geology and Early Industry in the Upper Housatonic Watershed (Earthview LLC)
After introductory chapters on Berkshire geology, Author Ed Kirby takes you to some of the most scenic and interesting sites throughout the Berkshires of Massachusetts, Connecticut, and New York. As you take the 25 field tours, which include roadside geology, hikes and short walks, you gain field experience with local geology and also appreciate the role geology played in the industrial and historical development of the region. With some humor and excellent illustrations, Ed presents the making of rocks and landscape, the workings of blast furnaces, localities of iron ore, glass sand, and clay. Quotes and stories from Longfellow, Melville, Hawthorne, and Wharton are interspersed with descriptions of unconformities, great faults, waterfalls, and mountaintop vistas.
Keywords: #ConnecticutValley; #EducationalResources; #MassGeology; #MassGeologyBooks; Berkshire; book; clay; dinosaurs; field trip guide; footprints; fossils; geologic history; glaciers; hilltown; hitchcock; housatonic; industry; lake; mesozoic; nNew England; site; valley; varves; western Massachusetts

Roadside Geology of Massachusetts (Mountain Press)
Roadside Geology of Massachusetts explores the geologic history behind the rocks and landforms visible from the state's highways, including tours of Cape Cod, Nantucket, Martha's Vineyard, Boston Harbor, and Mount Greylock. With this book as your guide, examine the eroded remnants of mountains shoved to towering heights by colliding continents 400 million years ago and learn how Ice Age glaciers formed such well- known historic features as Beacon Hill, Walden Pond, and Plymouth Rock.
Keywords: #EducationalResources; #Fieldtrips; #MassGeology; #MassGeologyBooks; book; field trip guide; geologic history; guidebook; roadside geology; site

Written In Stone: A geological history of the northeast United States (Black Dome Press)
In vivid, non-technical prose, Written in Stone traces the geological changes in the American northeast since the continent perched on the equator and dinosaurs were young. Grand events unfold as continents collide, oceans disappear, mountain ranges rise and fall, and mass extinctions decimate entire species. The events are grand, but the features of the landscape created by these events are as familiar as the hill behind your home, the rocks in the stone walls that enclose your yard, and the grains of sand on the beach where you go to swim. The history of the landscape is written in all the rocks and stones of the Northeast. This is an indispensable reference to an understanding of the forces that shaped our familiar landscape from Maine to New Jersey.
Keywords: #EducationalResources; #MassGeology; #MassGeologyBooks; book; field trip guide; geologic history; New England